Local development policy effects on environmental quality: the case of Amathole District Municipality - Kwangware, Thompson (Technium Social Sciences Journal, 2022)
Sustainability is a global problem which is practically difficult to implement. Pressure from Constitutional developmental obligations present enormous problems in South Africa, hampering the transitioning to sustainability at sub-national levels, where increased resources are required to compliment expertise amid negative effects of incoherent efforts and disaggregated planning that complicates the attainment of minimum sustainability levels. Data gathering is haphazard, making it impossible to get meaningful knowledge of baseline environmental conditions. This study galvanized professionals and academics to develop environmental quality indicators, gather data and conducted an assessment using Multi Criteria Analysis (MCA) to stimulate municipalities to implement sustainable policies and comply with national objectives. 6 municipalities were assessed for environmental quality using 25 locally relevant indicators. Information about the district levels of sustainability was provided by the results. The aim being transparency, objective self-assessment and reporting providing the basis for remedial action as recommended by Agenda 21 and NFES